2008
DOI: 10.1063/1.2985854
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a negative ion source. II. Plasma-gas coupling in the extraction region

Abstract: The production, destruction and transport of H -in the extraction region of a negative ion source are investigated with a 1D(z)-3V Particle-in-Cell electrostatic code. The motion of charged particles (e, H +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Different bulk collisions are implemented using Test Particle and Direct Simulation Monte Carlo Collision techniques [30]. The list of relevant collisions included are reported in [31].…”
Section: Description and Assumptions Of Numerical Modelmentioning
confidence: 99%
“…Different bulk collisions are implemented using Test Particle and Direct Simulation Monte Carlo Collision techniques [30]. The list of relevant collisions included are reported in [31].…”
Section: Description and Assumptions Of Numerical Modelmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] All the extraction region models [10][11][12][13] suffer from an important source of inconsistency: plasma injection condition from the source bulk region. In fact, in an almost collisionless sheath, there is no mechanism to redistribute the energy in parallel and perpendicular directions and therefore the plasma bulk boundary values of flow velocities are very important.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other modeling approaches, such as two-dimensional fluid models and particle-in-cell simulations using Monte Carlo collision models, have been used to analyze the reaction kinetics in hydrogen plasmas. [19][20][21][22][23][24][25] In all of the aforementioned hydrogen plasma global models, the EED was assumed to be Maxwellian. Some researchers have identified that a change in the electron energy distribution function (EEDF), i.e., from a Maxwellian EEDF to a non-Maxwellian EEDF, can affect the model results.…”
Section: Introductionmentioning
confidence: 99%